UPAYA MENINGKATKAN KESIAPAN MENJADI CALON GURU MELALUI SELF-EFFICACY DAN PENGUASAAN MATERI KULIAH KEPENDIDIKAN - Anggraeni, Anggun; Fikri, Faisal; Utama, Dian Herdiana (Comm-Edu (Community Education Journal), 2024)
One of the reasons for the low quality of education in Indonesia is the low quality of teaching staff (teachers). Based on data from the UNESCO Global Education Monitoring (GEM) Report 2016, the quality of teachers in Indonesia is ranked 10th out of 14 developing countries in the world, which is because readiness to become teachers in Indonesia is still low. Then, this research was also motivated by the still low readiness of student teacher candidates for the 2019 FPEB UPI economic education study program in facing their career, both in terms of their abilities and self-confidence. The aim of this research is to determine the influence of self-efficacy and mastery of educational course material in increasing readiness to become prospective teachers. The method used is an explanatory survey method using a questionnaire as a research instrument and data collection tool. The population and sample in this research were economic education students class of 2019 at the Indonesian Education University with a total of 90 students as respondents. The data analysis technique used is multiple regression. The research results show that, (1) self-efficacy has a positive effect on readiness to become a teacher candidate, (2) mastery of educational course material has no effect on readiness to become a teacher candidate.